The music during century of the masses (Music and society) 3 (Nóema, 2013)
The Beatles. Alex Ross: Listen to this. The destiny of music in the modern age. The mass-public. The young people, the culture and the music. The meaning of music and his fruition.
Keywords: The Young People; the Music; the Fruition